«Una propuesta experimental de material didáctico sobre la obra gráfica: El manual básico del grabado». - Martínez Córdoba, Carlos; Rubia Tejada, José María de la; López González, Francisco; Carpintero, Alfonso (Arte, Individuo y Sociedad, 1997)
Sin resumen